SEMINAR ON LITERACY BEGINS THROUGH DEEP LEARNING SEMINAR LITERASI MEMBACA PERMULAAN MELALUI DEEP LEARNING - Nita Priyanti; Mai Mutiah Tri Wahyuni, Isti Sarikasdani, Mulyani Putri, Neuneu Nur Alam, Eka Mitra Ningsih (JOURNAL OF COMMUNITY DEDICATION, 2025)
Improving early reading literacy in early childhood remains a critical challenge in education, especially under the demands of the Merdeka Curriculum, which emphasizes meaningful and child-centered learning. One relevant pedagogical approach is deep learning, which focuses on reflective thinking, critical engagement, and active student participation. This community service activity aimed to enhance the competencies of kindergarten teachers across Purwakarta Regency in designing and implementing early reading instruction based on the deep learning approach. The implementation method included interactive seminars, hands-on sessions, reflective discussions, and evaluations through pre-test and post-test assessments. A total of 50 teachers participated in this program. The results showed a significant increase in teachers’ understanding of early literacy concepts and their ability to apply deep learning strategies, with an average score improvement of 30%. In addition, positive changes in teachers' attitudes toward innovative teaching methods were observed through qualitative feedback and observation. This program demonstrates that the deep learning approach is effectively applicable in early childhood education settings and contributes to improving the quality of early literacy instruction. The study recommends continuous professional development, policy support from local education authorities, and the development of supporting learning media to strengthen the application of this approach. Therefore, this activity not only addresses the practical needs of teachers but also enriches pedagogical strategies in early childhood education.